Pengaruh Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan Pemerintah Daerah Kabupaten Manokwari - Anik Wuriasih; Etik Wahyuni; Syarifuddin (JFRES Journal of Fiscal and Regional Economy Studies, 2019)
This study aims to examine the influence of several factors of Internal Control Systems (control environment, risk assessment, control activities, information and communication, and monitoring) on the quality of local government financial statements. The population in this study are all working in SKPD Manokwari. The sample in this study is the head of department and the staff/employees of the financial part. Our sample are 45 respondents. The samples were selected by using a probability sampling method. Data was collected by distributing questionnaire to the respondents directly concerned. The results show that all independent variables of Internal Control System has a significant effect on the quality of local government financial statements. It then can be concluded that all element factor of Internal Control System is the most effective.